Effects of thiamethoxam seed treatments on soybean aphid (Hemiptera: Aphididae) feeding behavior - Stamm, M. D.; Heng-Moss, T. M.; Baxendale, F. P.; Reese, John C.; Siegfried, B. D.; Hunt, T. E.; Gaussoin, R. E.; Blankenship, E. E. (My University, 2013)
Since its discovery in North America in 2000, the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), has rapidly become an important pest of soybean [Glycine max (L.) Merrill], sometimes resulting in significant yield losses. Previous research has documented the toxicity of neonicotinoid seed treatments to soybean aphids, but control under field conditions has been inconsistent. Imidacloprid, a popular neonicotinoid insecticide, has been shown to exhibit antifeedant effects on aphids. Antifeedant activity has not been demonstrated for other neonicotinoids, including thiamethoxam. This research investigated the effects of a thiamethoxam seed treatment on soybean aphid feeding behavior by using electronic penetration graphs (EPG) to visualize stylet penetration behavior. Soybean aphid feeding behavior was assessed for 9 h on thiamethoxam-treated and untreated soybeans (V2 and V4 stages). Because results were inconclusive from initial experiments, a study was conducted to document the effects of thiamethoxam-treated soybeans on soybean aphid survival. The seed treatment was shown to negatively affect aphid survival at 4, 8, and 11 d after aphid introduction. A subsequent EPG study then was designed to document soybean aphid feeding behavior for 15 h, after an initial exposure of 9 h to thiamethoxam-treated soybeans. In this study, the exposed aphids exhibited significant differences in feeding behavior compared with those aphids feeding on untreated soybeans. Soybean aphids on thiamethoxam-treated soybeans spent significantly less time feeding in the sieve element phase, with a greater duration of nonprobing events. These studies suggest soybean aphids are unable to ingest phloem sap, which may be another important element in seed treatment protection.
Citation: Stamm, M., Heng-Moss, T., Baxendale, F., Reese, B., Sigfried, B., Hunt, T., Gaussoin, R., & Blankenship, E. (2013). Effects of Thiamethoxam Seed Treatments on Soybean Aphid (Hemiptera: Aphididae) Feeding Behavior. Journal of Economic Entomology, 106(6), 2384-2390. https://doi.org/10.1603/EC13268
Keywords: Soybean aphid; Thiamethoxam; Seed treatment; Electronic penetration graph